Institutional Ownership, Characteristics Of The Audit Committee And Information Power Earnings - I Nyoman Wijana Asmara Putra; Ni Made Dwi Ratnadi (Jurnal Akuntansi, 2018)
The objective of this research to test the effect of institusional ownership and committee audit characteristic on the informativeness of earnings. Especially this research to test the non-banking institusional ownership, banking institusional ownership, independent commissioner as the member of audit committee, competence a member audit commitee in accounting and financial, and frequency of meeting held by audit committee. The data is taken from secondary sourced from the Indonesian Stock Exchange. Data were analyzed using multiple regression. The result indicates that, the non-banking institutional ownership, and shareholding by banks positive effect on the informativeness of earnings. Competence audit committee members in the fields of accounting and finance, and frequency of meetings held positive effect on informativeness of earnings. However, the proportion of independent directors on the audit committee does not affect to the earnings informativeness.